PERSEPSI PENDENGAR RADIO MADAMA FM TERHADAP PROGRAM HOLYROXX DALAM MENGENALKAN MUSIK INDIE DI KOTA MAKASSAR - Azzahra Anwar p, Putri; Zelfia, Zelfia; Muttaqin Mustari , Andi (UNIVERSITAS MUSLIM INDONESIA, 2022)
This study aims to: find out the perception of madama fm radio listeners to the holyroxx program in introducing indie music in the city of Makassar and the form of the holyroxx program in introducing indie music in the city of Makassar. This research uses descriptive analysis qualitative research method, with the research location in Makassar City, South Sulawesi. Data collection is the technique of observation, interviews and documentation. Data analysis was carried out by collecting data, reducing, presenting data and drawing conclusions. The results show that the listener's perception is different for each individual depending on their respective personalities, the form of the holyroxx program is supported through various inhibiting factors generated by the technical influence on the perception and supporters in the listener's perception with the existence of a platform supported by an informative announcer.